Downregulation of LRP/LR with siRNA inhibits several cancer hallmarks in lung cancer cells. Issue 2 (13th January 2023) - Bignoux, Monique J.; Otgaar, Tyrone C.; Bernert, Martin; Weiss, Stefan F. T.; Ferreira, Eloise
Abstract : The incidence and mortality rates of cancer are growing rapidly worldwide, with lung cancer being the most commonly occurring cancer in males. Human carcinomas circumvent the inhibitory pathways induced by DNA damage and senescence through the upregulation of telomerase activity. The 37 kDa/67 kDa laminin receptor (LRP/LR) is a cell surface receptor which plays a role in several cancer hallmarks, including metastasis, angiogenesis, cell viability maintenance, apoptotic evasion, and mediating telomerase activity. We have previously shown that the knockdown of LRP/LR with an LRP‐specific siRNA significantly impedes adhesion and invasion, induces apoptosis, and inhibits telomerase activity in various cancer cell lines in vitro . Here, we investigated the effect of downregulating LRP/LR with LRP‐specific siRNA in A549 lung cancer cells. Downregulation of LRP/LR resulted in a significant decrease in cell viability, migration potential, and telomerase activity, as well as a significant increase in apoptosis. Proteomic analysis further suggested the re‐establishment of immune control over the lung cancer cells, a previously unidentified facet of LRP downregulation in cancer. Altogether, we suggest that targeting LRP/LR for downregulation may have therapeutic potential for inhibiting several cancer hallmarks. Abstract : LRP/LR is overexpressed in many cancer cell types and is associated with various cancer‐promoting processes. In this study, we downregulated LRP/LR in lung cancer cells and showed that this strategy has a four‐fold function in impeding key cancer hallmarks in the lung cancer cells, which therefore has the potential for improving the prognosis of those suffering from lung cancer.